Consumer Perception Regarding Demand of Branded Shoes - Deepak Kumar Chachda; Dr Kavita A. Jain (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The current study deals with the objective “How to Consumer Preception Regarding Demand of Branded Shoes”. In this study we observed that how to consumer perception impact on demand for branded products like shoes. in this study also to know how culture, income, social status, life style, Peer pressure and other factors impact on the demand of branded shoes. In the modern era technology is growing fastly. They directly affect on our thinking process and they result represent our demand is also change as per time to time. We can say that our perception related to product change very soon. In this study we discuss only some points. The information of the study could be further used by the researchers and practitioners for conducting future studies in the similar area.
Keywords: Branded Shoes; Consumer Perception; Culture, Income; Peer Pressure